Self-Regulation In Learning New Students At Ma'had Al - Jami'ah UIN Kiai Haji Achmad Siddiq Jember - Widodo, Arif; Zain, Mahmud; Rohmi, Putri Kamilatul (IJIBS, 2023)
The period of accepting new students at Mah'ad Al-Jami'ah UIN KH Achmad Siddiq Jember has an impact on the psychology of students in carrying out adjustments in learning Islamic boarding school life. Santri as adult educated people are required to have initiative, strategy, management and evaluation of their own learning so that their goals can be achieved. Self-regulation of students in learning in psychological studies is called Self Regulated Learning. Based on the results of the interviews, there were still students who had not carried out self-regulated learning properly. The purpose of this research is to explore the motivations, strategies, metacognitive and management of new student santri resources in carrying out self-adjustment in learning mah'ad life. This research was conducted at Ma'had Al - Jami'ah KH Achmad Siddiq State Islamic University Jember using qualitative research methods. Research data obtained through interviews and documentation. The research subjects were new student students. The results of the study found the following; (1) New student students' learning motivation is divided into intrinsic and extrinsic motivation. (2) Learning strategies for new students using sorogan and dialogue (3) Metacognitive learning for new students maximizing basic skills (4) Managing new student santri resources is done by asking for help from friends and Muslim teachers/ustadzah when having difficulty mastering the material. (5) factors that influence new student students in self-regulation in learning on adjustments at Mah'ad Al - Jami'ah KH Achmad Siddiq State Islamic University Jember include personal, behavioral and environmental factors